Case report: horse or zebra, ascites or pseudo-ascites? Care for pictural details! - Alessandro Rossi; Fabiola Di Dato; Raffaele Iorio; Gianfranco Vallone; Carmine Mollica; Maria Grazia Caprio; Jean De Ville De Goyet; Maria Immacolata Spagnuolo (BMC, 2019)
Abstract Background Pseudo-ascites is a very rare condition in children and remains a challenging diagnosis. Targeted imaging may be helpful, but a high index of clinical suspicion is often necessary to guide the investigations, as pseudo-ascites may efficiently mimic true ascites. To date, still many cases of pseudo-ascites suffer diagnostic and therapeutic delay, and some are only diagnosed during surgical exploration. We report the case of a patient with a late laparoscopic diagnosis of pseudo-ascites. We retrospectively review our patient's imaging findings and suggest new characteristic features which may help differentiate pseudo-ascites from true ascites. Case presentation A 7-month-old infant was referred for a progressive abdominal distention. Physical examination and initial ultra-sonographic findings evoked free ascites. An extensive diagnostic workup was then performed and was negative for hepatic, renal, cardiac, intestinal, pancreatic, inflammatory or infectious diseases, malignancy and congenital metabolic disorders. Pseudo-ascites was evoked and dedicated ultra-sonographic and magnetic resonance studies were repeated but could not confirm this diagnosis. Symptomatic diuretic treatment with spironolactone and furosemide was then started. A temporary and limited effect was noted but, with time, repeated paracenteses were necessary as the abdominal distention progressed causing discomfort and breathing difficulty. Last, because the patient's quality of life deteriorated, a peritoneal-venous shunting was proposed; as the operation started with a diagnostic laparoscopy, a benign giant cystic mesenteric lymphangioma was identified and totally excised. The resolution of symptoms was immediate and the patient remained symptom-free throughout the subsequent observation period that lasted more than 1 year. Conclusions Increased awareness about pseudo-ascites is necessary, as the diagnosis is often overlooked, and treatment delayed. Targeted imaging may be helpful, as some specific, although not pathognomonic, features exist which may aid in the diagnosis.